Designing HR Enhancing CSR for Wealth Redistribution: A Study on Banking Sector of Bangladesh - Ara, Nusrat; Rabby, Anik Hassan (Maroon Journal De Management, 2024)
The focus in this case study is drawn on the issue of economic accountability in corporate social responsibility. Therefore, an attempt is made to evaluate the extent to which human resources (HR) may influence CSR to assume economically understanding projects and define the role of HR in influencing employee and external stakeholder attitudes and behaviours. To this end, the research analyzes the relationship between HR-centric CSR practices and wealth creation outside the company premises. There are few empirical studies on that kind of influence and earlier studies have shown that HR does have the potential to influence organisational initiatives but the employes are more likely in their traditional roles. Therefore, there is a fair amount of latent potential that is underexploited. To explain these interrelations in the banking sector, three hypotheses are developed. Internal consistency is measured using Cronsoh 7s alpha, which indicate an acceptable result toward 1 human resource policy: 0.924 < 1; Corporate social responsibility: 0.973 < 1; and the effect of a human resource policy and corporate social responsibility on redistribution of wealth: 0.983 < 1. These findings support the reliability of constructs. Regression analysis is used to ensure the explanatory adequacy of the theoretical model, with the result indicating an R 2 of 86 percent. All three correlation tests show statistical relationships indicating that when HR is allowed increased autonomy, it can wield significant impacts of organisational outcomes such as employee motivation to policy implementation.